Production of High-Grade Antimony Oxide From Smelter Slag via Leaching and Hydrolysis Process - Ibrahim, Ahmedaljaali Ibrahim Idrees; Aboelgamel, Muhammed; Soylu, Kartal Kaan; Top, Soner; Kursunoglu, Sait; Altiner, Mahmut; Ibrahim Idrees Ibrahim, Ahmedaljaali; Kaan Soylu, Kartal (Elsevier, 2025)
This study aimed to investigate the recovery of antimony (Sb) from slag generated in an antimony smelting plant using leaching followed by hydrolysis processes. The leaching behaviors of rare earth elements (REEs) were also examined. The physicochemical properties of the slag were determined using various analytical techniques. The slag (4.12 % Sb) was mainly composed of quartz and minor minerals, including microline, magnetite, heden-bergite, and stibiconite. The Sb types in the slag determined by XPS were found to be in the oxide form. The concentrations of REEs (La, Y, Ce, and Nd) in the slag were 169.21 g/t. Preliminary leaching experiment results indicate that (i) HCl was selected rather than other acids due to its high extraction ability on the Sb from the slag, (ii) a sample with a d50 of <25 mu m should be used, (iii) the slurry should be mixed at 300 rpm. In the following leaching tests, the effects of leaching parameters (HCl acid concentration, amount of tartaric acid, solid-to-liquid ratio, reaction temperature, and time) on the extraction rates of Sb, impurities, and REEs were investigated. At the best leaching conditions (HCl: 8 M, amount of tartaric acid: 1 g/L, stirring speed: 300 rpm, reaction tem-perature: 75 C-degrees, and time: 180 min), the extraction rates of Sb from the slag were determined to be 91.19 %, but the extraction rates of REEs were measured to be <= 50 %. The activation energy (Ea) for Sb leaching was found to be 46.75 kJ/mol, indicating that the reaction was governed by the chemically controlled mechanism. In particular, it was understood from the additional experimental results that the leaching procedure should be carried out for 20 h to extract La with an extraction rate of >90 %. However, the extraction rate of Sb was negligible in extended times. It was determined that using tartaric acid positively affected La's leaching mech-anism, and the required leaching time for La decreased to 180 min from 20 h with the increase of tartaric acid from 1 g/L to 6 g/L. Hydrolysis tests were conducted using the Taguchi approach (L32, 2<^>1 4<^>3). The effects of the alkaline type (NH4OH and NaOH), stirring speed (100, 200, 300, and 400 rpm), temperature (50, 60, 70, and 80 C-degrees), and pH (1.5, 2, 2.5, and 3) on the precipitation of Sb from the PLS were investigated. NH4OH was suggested for use in the hydrolysis test to obtain precipitates with higher purities. The product obtained under the optimal conditions comprised 81.43 % Sb, 16.23 % O, and 2.34 % Fe. The product was identified as antimony oxide by XRD
Kursunoglu, Sait/0000-0002-1680-5482;
Keywords: Antimony; Smelter Slag; Hcl Leaching; Hydrolysis; Rare Earth Elements